LIBS Analysis of Industrial Composite Materials - Pereira-Filho, Edenir Rodrigues; Pereira, Fabiola Manhas Verbi [UNESP]; Machado, Raquel Cardoso; de Andrade, Daniel Fernandes; Babos, Diego Victor; Garcia, José Augusto; Sperança, Marco Aurélio; Gamela, Raimundo Rafael (Springer Nature, 2025)
The rapid advancement of stable high-power laser sources, efficient broadband spectrometers, and fast, sensitive detection systems has significantly propelled research in laser-induced breakdown spectroscopy (LIBS). Beyond traditional laboratory use, LIBS has become a vital tool for quality inspection in large-scale industrial production. Complemented by evolving algorithms and computational platforms, LIBS now facilitates efficient data normalization, outlier detection, preprocessing, and calibration strategies. These advancements have broadened its utility and enhanced analytical precision. LIBS instruments designed for industrial applications are categorized into portable and transportable systems. Portable systems, compact and battery-operated, are user-friendly and enable single-user operation. Conversely, transportable systems, resembling laboratory setups, require vehicle transportation and multiple operators. Over the past decade, portable LIBS devices have gained popularity, particularly in primary and secondary metal industries, where rapid material identification and compositional analysis are essential. These analyzers are indispensable for quality control in the production of metal alloys, glass, photovoltaic silicon, and microelectronics. They also play a pivotal role in recycling by enabling real-time identification of metals and alloys for efficient sorting. Inline LIBS applications, particularly in metallurgical processes like steel and alloy production, further improve its industrial relevance. With real-time analytical capabilities, LIBS enhances decision-making and operational efficiency, reinforcing its significance across diverse industrial sectors.